Pengaruh Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Pengurus Lembaga Kemahasiswaan: Studi Kasus pada UKM LKIMB Universitas Negeri Makassar Periode 2022-2023 - Azrizan Bin Asdar; Anwar Anwar; Romansyah Sahabuddin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to find out how leadership style and organizational culture influence the performance of the management of the Student Activity Unit of the Institute for the Scientific Study of Faithful Students, Makassar State University (UKM LKIMB UNM) for the 2022-2023 period. The total population and sample used was 43 administrators. Data collection was carried out using observation and questionnaires. The data analysis technique carried out was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 26. The results of this research show that leadership style partially has a negative and significant influence on management performance. Meanwhile, organizational culture has a positive and significant influence on management performance. The leadership style and organizational culture simultaneously have a significant influence on management performance.